Library experiences of Hurricane Katrina and New Orleans Flood survivors - Braquet, Donna M. (2021)
More than one million residents were displaced by Hurricane Katrina and the New Orleans Flood. Uprooted from their lives and dispersed across the country, survivors found themselves hundreds of miles away from home. Some found comfort and much needed information in public libraries. This article discusses the library experiences of survivors as revealed through an online survey and in-depth interviews. The study, conducted from August to October of 2006, found that nearly one-half of survey respondents and 40% of interviewees used libraries following the disasters. The reasons for their visits included Internet access, information and technology assistance, mental escape, and refuge. Participants also discussed how the destruction of libraries added to their sense of loss and how the restoration of libraries gave them a sense of hope.